2013
DOI: 10.12954/pi.12009
|View full text |Cite
|
Sign up to set email alerts
|

Simple method for preventing inguinal hernias after radical retropubic prostatectomy

Abstract: Purpose:Inguinal hernias often occur after radical retropubic prostatectomy (RRP). We present a novel and simple technique for preventing inguinal hernias after RRP, which any surgeon can complete within a few minutes.Methods:A total of 230 Japanese prostate cancer patients underwent RRP between January 2007 and September 2011. From July 2009, 115 patients underwent inguinal hernia prevention procedures at the same time as RRP. In this procedure, we released approximately 5 cm of the bilateral vas deferens and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hori et al bluntly detached peritoneum at the internal ring so as to isolate spermatic cord, merely 3% of RRP patients in prevented group developed PIH compared to 19% in non-prevented group [ 27 ]. Another effective procedure, opening the spermatic sheath and releasing approximately 5 cm bilateral vas deferens and spermatic vessels from the peritoneum, resulted in 0.87% PIH rate in prevented group while 15.7% non-prevented patients suffered from PIH, was introduced by Koike in 2013 [ 28 ]. The conceivable principle of these manipulations was that the scar tissues formed by isolating the spermatic cord could easily help to strengthen the internal ring.…”
Section: Discussionmentioning
confidence: 99%
“…Hori et al bluntly detached peritoneum at the internal ring so as to isolate spermatic cord, merely 3% of RRP patients in prevented group developed PIH compared to 19% in non-prevented group [ 27 ]. Another effective procedure, opening the spermatic sheath and releasing approximately 5 cm bilateral vas deferens and spermatic vessels from the peritoneum, resulted in 0.87% PIH rate in prevented group while 15.7% non-prevented patients suffered from PIH, was introduced by Koike in 2013 [ 28 ]. The conceivable principle of these manipulations was that the scar tissues formed by isolating the spermatic cord could easily help to strengthen the internal ring.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, several surgical procedures have been proposed for post-RARP IH prevention. Some researchers have proposed separating the processus vaginalis from the perineum and/or vas deferens [21][22][23][24]. Lee et al reported a simple method in cases of patent processus vaginalis (PPV) which consists of transecting the PPV, plugging a hemostatic agent into the detached canal end, and suture closing the internal inguinal oor [25].…”
Section: Discussionmentioning
confidence: 99%
“…Various surgical procedures have been proposed as means of preventing IH after RARP, including separating the processus vaginalis from the perineum and/or the vas deferens [21][22][23][24], plugging hemostatic agents into the inguinal canal and suture closing the internal inguinal ring (IIR) [25], su ciently incising the peritoneum around the IIR, separating the spermatic vessels, and dissecting and cutting the vas deferens [19,26]. However, none of these methods have been established or standardized for RARP.…”
Section: Introductionmentioning
confidence: 99%
“…Hori et al bluntly detached peritoneum at the internal ring so as to isolate spermatic cord, merely 3% of RRP patients in prevented group developed PIH compared to 19% in non-prevented group [28]. Another effective procedure, opening the spermatic sheath and releasing approximately 5 cm bilateral vas deferens and spermatic vessels from the peritoneum, resulted in 0.87% PIH rate in prevented group while 15.7% non-prevented patients suffered from PIH, was introduced by Koike in 2013 [29]. The conceivable principle of these manipulations was that the scar tissues formed by isolating the spermatic cord could easily help to strengthen the internal ring.…”
Section: Discussionmentioning
confidence: 99%